2017
DOI: 10.1007/s11655-017-2544-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Ilex hainanensis Merr. exhibits anti-melanoma activity by induction of G1/S cell-cycle arrest and apoptosis

Abstract: IME exhibited significant anti-melanoma activity in vitro and in vivo, suggesting that IME might be a promising effective candidate with lower toxic for malignant melanoma therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, curcumin, bark hormone, oridonin, matrine, and oleanolic acid have shown strong antitumor activity in preclinical studies 14. Moreover, studies have demonstrated that IME exhibited significant antimelanoma activity in vitro and in vivo 15…”
Section: Discussionmentioning
confidence: 99%
“…In addition, curcumin, bark hormone, oridonin, matrine, and oleanolic acid have shown strong antitumor activity in preclinical studies 14. Moreover, studies have demonstrated that IME exhibited significant antimelanoma activity in vitro and in vivo 15…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is no deleterious side effect on melanoma when nanomolar TTX is applied as a pain-killer. On the other hand, TTX is used to identify Na + channel subtypes ( 22 , 23 ). While Na v 1.5 had a median effective concentration of TTX at 5.7 µM, the median effective concentrations of TTX to Na v 1.8 and Na v 1.9 are 60 and 40 µM respectively ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other species, such as I. asprella [9] and I. hainanensis Merr. [35], are used as folk medicines. More than 20 Chinese Ilex species have medicinal uses recorded [36].…”
Section: Hollies Utilized As Sources Of Medicinesmentioning
confidence: 99%